A material odyssey for 3D nano/microstructures: two photon polymerization based nanolithography in bioapplications. (June 2020) - Liao, Caizhi; Wuethrich, Alain; Trau, Matt
Highlights: Functional three-dimensional (3D) miniaturized constructs hold great potential for bio-relevant applications. Ultrafast laser nanolithography, in particular two photon polymerization (TPP) nanolithography platform, afford to generate accurate 3D nano/microscopic structures. Photosensitive materials play a central role in building 3D micro/nanostructures for bio-applications. This comprehensive review discusses critically a broad spectrum of photosensitive materials based on their uses in bio-applications. Abstract: Functional three-dimensional (3D) microscopic and nanoscopic structures have the potential to significantly drive the development of innovative bioapplications. As the only 3D prototyping technique for precise and controllable additive manufacturing of sub-100 nm structures, femtosecond laser based nanolithography including two-photon polymerization (TPP) has attracted significant interest. Central to the TPP fabrication process is the cross-linking of the photosensitive material that builds the construct of the functional 3D micro/nanostructures. Driven by the development of biocompatible photosensitive materials for TPP fabrication, significant progress has been achieved in cell engineering, tissue engineering, drug delivery, microfluidics, and biosensing. This review features a comprehensive and material-focused account on the latest advancements in TPP nanolithography for bioapplications for the first time. After a brief introduction of TPP, the review discusses critically photosensitive materials including SU-8, IP resists, PEG-based hydrogels, protein-based biomolecules, hybrid inorganic–organic materials, and others. Finally, current achievements, fabrication limitations, and opportunities for the advancement of TPP-based functional 3D microscopic and nanoscopic materials are summarised. Graphical abstract: Image, graphical abstract